REFORMASI BIROKRASI PELAYANAN PUBLIK YANG SEJALAN DENGAN KONSTITUSI DAN PRINSIP DEMOKRASI - Rizal Nurdin Ismail Nurdin; Isa Anshori (Prodi PPkn Universitas Slamet Riyadi, 2022)
The implementation of democracy in the management of public services is an important part that must be carried out by the bureaucracy. In its implementation, it must uphold democratic principles that are in line with the state constitution, namely freedom/equality, people's sovereignty, and open and responsible government. Better and more satisfying services for the community must be carried out by public service providers. The government's attitude is still inclined to only provide good services to certain people, who have the same political views and thoughts as the government. The paradigm of the management of the administration of the public service bureaucracy must be changed, which initially